Three new gastrotrich species of the genus Tetranchyroderma (Macrodasyida: Thaumastodermatidae) from Korea - Lee, Jimin; Chang, Cheon Young (Zootaxa, 2012)
Three new gastrotrich species of the genus Tetranchyroderma are described sublittoral sandy bottoms of the Yellow Sea and Jeju Island in South Korea. Tetranchyroderma aethesbregmum sp. nov., which has a dorsal cuticular armature with pentancres only, is characterized by the peculiar shape of the head with a median trapezoidal lobe flanking three pairs of papillae. Tetranchyroderma megabitubulatum sp. nov. is clearly differentiated from other pentancrous species by the character combination of three pairs of cephalic tentacles, a pair of long dorsolateral adhesive tubes, and paired ‘foot’ ventral adhesive tubes. Tetranchyroderma insolitum sp. nov. is the only species possessing cuticular armature with tetrancres and triancres mixed, and also characteristic in having an earlobeprotrusion at the posterolateral corners of head.